2017
DOI: 10.1155/2017/5246080
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Femoral Fracture in Hip Arthrodesis Treated with Double Reconstruction Plates

Abstract: We present a rare clinical case of a 90-year-old female who sustained a proximal femoral neck fracture following long-standing hip arthrodesis. Since the fracture occurred relatively proximally and involved the pelvis, double-plate fixation was chosen to achieve rigid fixation. The reconstruction plate was placed at the posterior and anterior columns individually through single vertical incision. She was treated successfully, and she attained preinjury activity level. Proximal femoral fractures in arthrodesed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There are a few available reports regarding proximal femoral fractures in arthrodesis or spontaneous fused hip joints [10][11][12][13][14][15][16][17][18][19][20]. Sponseler et al reported in 1984 that the rate of proximal femoral fracture in this condition was 73% (2/53 cases) [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are a few available reports regarding proximal femoral fractures in arthrodesis or spontaneous fused hip joints [10][11][12][13][14][15][16][17][18][19][20]. Sponseler et al reported in 1984 that the rate of proximal femoral fracture in this condition was 73% (2/53 cases) [9].…”
Section: Discussionmentioning
confidence: 99%
“…The fractured fragment was divided into two fragments, which consisted of the pelvis with proximal femur as the proximal fragments and the distal femur with the long lever arm of the lower extremity as the distal fragment. The large rotational stress and the shear stress were produced at the fracture site until bony fusion was performed [11,20]. Therefore, it was difficult to maintain sufficient stability with conservative treatment to achieve bony fusion; thus, there have been no reports that recommend conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations